Ulnar Nerve Conduction Abnormalities in Turkish Taxi Drivers - Sevgi İkbali AFŞAR and Nuri ÇETİN and Şehri AYAŞ and Gamze Akın MUMCU and Metin KARATAŞ (Archives of Rheumatology, 2014)
Objectives: This study aims to investigate the presence of ulnar entrapment neuropathy at the elbow in taxi drivers, and possible relationship between ulnar entrapment neuropathy and habitually leaning the left elbow on the lower edge of the window. Patients and methods: The study was performed between December 2008 and February 2009 in Ankara and included 40 male taxi drivers (mean age 35.5±7.3 years; range 25 to 54 years) and 40 healthy male controls (mean age 33.6±6.1 years; range 25 to 54 years). Nerve conduction studies were performed on both upper limbs of all participants. Results: Left side motor and sensory nerve conduction velocities at the elbow segment of the ulnar nerve were significantly decreased, while F latency of the ulnar nerve was significantly prolonged in taxi drivers. Motor and sensory conduction velocity over both left and right ulnar nerve at the elbow segment were significantly decreased, while F latency of the ulnar nerve was significantly prolonged in the taxi drivers compared to the control group. Ulnar nerve conduction parameters and F latency on both sides were statistically similar in the non-leaning group of taxi drivers; however, motor and sensory conduction studies over the left side of the ulnar nerve elbow segment were slower and F latency was longer in the leaning group of taxi drivers, compared to the right side and to the non-leaning group of taxi drivers. Conclusion: Prolonged elbow flexion and habitually leaning the left elbow may cause electrodiagnostically diagnosed ulnar entrapment neuropathy in taxi drivers.